Conditional Survival in Patients With Rectal Cancer and Complete Clinical Response Managed by Watch and Wait After Chemoradiation: Recurrence Risk Over Time. Issue 1 (July 2020) - São Julião, Guilherme P.; Karagkounis, Georgios; Fernandez, Laura M.; Habr-Gama, Angelita; Vailati, Bruna B.; Dattani, Mit; Kalady, Matthew F.; Perez, Rodrigo O.
Abstract : Objective: Analyze conditional recurrence-free survival (cRFS) for rectal cancer patients with complete clinical response (cCR) after neoadjuvant chemoradiation (nCRT) managed nonoperatively after each year without recurrence. Summary Background Data: Select patients with cCR after nCRT have been managed nonoperatively. Risk factors for local recurrence, the need for prolonged follow-up, and the risk of recurrence over time are not well defined. Methods: Retrospective review of patients with rectal cancer cT2-4N0-2M0 treated with nCRT. Mean follow-up was 64 months. Patients who achieved cCR were managed nonoperatively. cRFS was used to investigate the evolution of recurrence-odds, as patients remain recurrence-free after completion of nCRT. Three-year cRFS was estimated at "x" years after completion of nCRT based on the formula cRFS3 = RFS(x+3) /RFS(x) . Results: One hundred ninety-seven patients with cCR after nCRT were included. Overall survival and recurrence-free survival (RFS) at 5 years were 81.9% (95% CI 74.0%–87.6%) and 60.4% (95% CI 52.5%–67.4%) respectively. Using cRFS estimates, the probability of remaining disease-free for an additional 3 years if the patient survived without disease at 1, 3, and 5 years, was 77.4% (95% CI 68.8%–83.8%), 91.0% (95% CI 81.9%–95.7%), and 94.3% (95% CI 82.9%–98.2%), respectively. In contrast, actuarial RFS rates for similar intervals were 79.1% (95% CI 72.5%–84.2%), 64.2% (95% CI 56.5%–70.8%), and 60.4% (95% CI 52.5%–67.4%). After 2 years disease-free, 3 year cRFS became similar for T2 and T3 cancers. In contrast, patients undergoing extended nCRT became less likely to develop recurrences only after initial 2 years of successful organ-preservation. Conclusions: Conditional survival suggests that patients have significantly lower risks (⩽10%) of developing recurrences after 2 years of achieving cCR following nCRT.